Crossing the midline: An exploration of reference frame conflict - Cadieux, Michelle L. (My University, 2013)
Multiple reference frames are used to interact with our surroundings. When these reference frames are in conflict, processing errors can occur. For tactile stimuli, this conflict is highlighted when the hands are crossed over the midline of the body. In this posture, vibrotactile temporal order judgments (TOJs) presented to the hands are impaired compared to an uncrossed posture. This decrease in temporal processing is known as the crossed-hands deficit. The deficit was explored in depth throughout this thesis. In Chapters 2, 3 and 4 different elements of the crossed-hands deficit were evaluated including its connections to the rod and frame test, individual and sex differences within the TOJ task, as well as the influence of vision and body position. These elements were framed with underlying goal of investigating the root cause of the deficit. The data presented here provided evidence for a conflict model of crossed hands processing. A conflict between the internal and external reference frames produced the deficit in temporal processing when the hands were crossed. The role of the body’s midline in understanding multisensory integration was further considered in Chapter 5 through the rubber hand illusion, which is a visuotactile phenomenon whereby an unseen real hand is mislocalized towards a seen rubber hand. When the real hand, rubber hand, or both were crossed over the midline the illusion did not occur. It was hypothesized that a failure to integrate the tactile information presented to the real hand with the visual rubber hand was responsible for the absence of the illusion. Taken together, the data presented in this thesis contribute to the greater understanding of how reference frame conflicts are resolved, particularly when the conflict occurs across the body’s midline.
Keywords: reference frame; midline; crossed-hands; egocentric; allocentric; rubber hand illusion; temporal order judgments; vision; tactile; sex difference; Cognition and Perception; Cognition and Perception